Basic Hip Arthroscopy: Diagnostic Hip Arthroscopy - Stone, Austin V. (Arthrosc Tech, 2017)
Hip arthroscopy is increasing in popularity for the diagnosis and management of hip preservation. The basics of hip arthroscopy positioning, fluoroscopic assessment, and portal establishment are reviewed in the first 2 parts of this series. This article is the third installment in which we describe a systematic approach to performing a diagnostic hip arthroscopy. A mastery of diagnostic arthroscopy is necessary for surgeons treating hip disorders.